Pengaruh Pengalaman Kerja, Pelatihan, dan Motivasi Kerja Karyawan dalam Meningkatkan Kinerja Karyawan - Nafisatul Ilim; A.Khairul Wahyudi; Fadlan Kurniadi; Siti Hairunnisa; M.Isa Anshori (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The existence of humans in an organization has a very vital position. The success of an organization is largely determined by the quality of the people who work in it. Rapid changes in the environment require their ability to capture these changing phenomena, analyze their impact on the organization and prepare steps to deal with these conditions. This journal is descriptive analysis. This method solves problems by describing and analyzing them, then looking for solutions to the problem based on the results of the literature review. Apart from that, there are several authors' points of view which are used as a basis for finding solutions to problems based on the results of the literature review. Apart from that, there are several author's points of view which are used as explanations to find solutions to the problem of work experience on employee performance. The definition of work experience consists of several types provided by experts. Experience in all activities is very necessary because experience is the best teacher. The meaning of this is that a person learns from the experiences they have experienced. HR management is the science and art of managing the relationships and roles of the workforce so that they are effective and efficient in order to help realize the Company's goals. They also need to implement workplace practices that are based on upholding fundamental rights in the workplace and international university standards, and fostering good HR management relationships as important for increasing productivity and decent work.